Biological effects of secondary metabolites of Inula racemosa on the parasitoid Bracon hebetor. Issue 8 (27th May 2021) - Kaur, Mandeep; Saraf, Isha; Kumar, Rakesh; Singh, Inder Pal; Kaur, Sanehdeep
Abstract: Secondary plant metabolites play an important role in mediating interactions among plants, insect herbivores, and their parasitoids. These defensive compounds not only affect the growth and development of herbivores, but also influence their natural enemies. In the present study, the diet‐mediated effect of hexane extract of Inula racemosa (Hooker fil.) (Asteraceae) was evaluated on the growth and development of the gregarious ectoparasitoid Bracon hebetor (Say) (Hymenoptera: Braconidae) using a polyphagous pest, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae), as its host. The influence of various concentrations of I . racemosa extract was recorded on B. hebetor 's parasitization behavior on its host larvae. The parasitism rate of naive female wasps decreased significantly when host larvae were reared on treated diet, but no adverse effect of plant extract was recorded on the viability of eggs. Detrimental effects of the plant extract were also detected in the form of reduced survival and delayed development of the parasitoid. Ingestion of hexane‐extract‐supplemented diet by S. litura adversely affected the emergence and parasitism rate of adults from the first generation of B. hebetor . In conclusion, consumption of I. racemosa extract by S. litura had a negative impact on various biological parameters of B. hebetor, although lower concentrations of plant extract had no adverse effects. There is a need to study the possible effects of secondary metabolites on these trophic interactions under natural conditions. Abstract : The effect of hexane extracts of Inula racemosa (Asteraceae) was evaluated on growth and development of the cosmopolitan gregarious ectoparasitoid Bracon hebetor (Hymenoptera: Braconidae) using a polyphagous pest, Spodoptera litura (Lepidoptera: Noctuidae) as its host. The parasitism rate of naive female wasps decreased when host larvae were reared on treated diet. Detrimental effects of the plant extract were also detected in the form of reduced survival and delayed development of the parasitoid.